2008
DOI: 10.1007/s10562-008-9569-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Ethane to Ethylene with Carbon dioxide over Cr–Ce/SBA-15 Catalysts

Abstract: Chromium oxide supported on SBA-15 was modified with Ce species by an incipient method. The effect of Ce on the activity of Cr/SBA-15 catalyst in the dehydrogenation of ethane with CO 2 was investigated. The activity is enhanced for Ce modified Cr/SBA-15 catalyst for the dehydrogenation of ethane with CO 2 . The cycle between Cr 6+ and Cr 3+ species can be carried out viaing the dehydrogenation of ethane and oxidation of CO 2 processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 43 publications
(50 reference statements)
1
55
0
Order By: Relevance
“…These ceria-containing catalysts have been studied in CO oxidation, water-gas shift reactions and catalytic partial oxidation of methane [27e29]. The effect of Ce on the activity of Cr/SBA-15 catalyst in oxidative dehydrogenation of ethane to ethylene was investigated by Shi [30]. It was found that adding Ce species to Cr/SBA-15 catalysts remarkably changed the redox properties and enhanced the catalytic activity of Cr species in catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…These ceria-containing catalysts have been studied in CO oxidation, water-gas shift reactions and catalytic partial oxidation of methane [27e29]. The effect of Ce on the activity of Cr/SBA-15 catalyst in oxidative dehydrogenation of ethane to ethylene was investigated by Shi [30]. It was found that adding Ce species to Cr/SBA-15 catalysts remarkably changed the redox properties and enhanced the catalytic activity of Cr species in catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The change of Cr from a higher oxidation state to lower oxidation state was found to influence the catalyst behavior [12]. The ODH of ethane with CO 2 was successfully carried out over the Cr-based catalysts prepared by using FeCrAl alloy foil as support [13] [19]. In the present investigation, FT-IR, UV-DRS, Raman and X-ray photoelectron spectroscopic investigations have revealed that the surface Cr species are mainly Cr 6?…”
Section: Catalytic Activitymentioning
confidence: 58%
“…The decrease in pore volume is due to partial blockage of the mesopores of SBA-15 after anchoring of CrO x species on to the surface. During this process some pore wall collapse might have taken place in the SBA-15 structure leading to the decrease of the pore diameter, as reported by Shi et al [19]. The phenomenon of non-closure of adsorption and desorption can be observed from the isotherms which can be explained as follows.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Regarding Cr catalyst, Hakuli et al reported that 14-16 wt% CrOx/Al2O3 showed high selectivity on dehydrogenation of isobutane and longer catalyst life 12) . Shi et al reported that 5 wt% Cr _ 10 wt% Ce/SBA-15 catalysts are effective for oxidative dehydrogenation of ethane and exhibited high conversion and ethylene selectivity 13) . On the other hand, Ga is known to have high catalytic activity in dehydrogenation and oxidative dehydrogenation of propane.…”
Section: Hmentioning
confidence: 99%